Manufacturer Behavior: In the Perspective of Islamic Economic and Conventional Economics - Adi, Mukhtar Adinugroho; Riyan Sisiawan; Zujajatul 'Ilmi (Journal of Islamic Civilization, 2022)
This study discusses the Theory of Producer Behavior in Islamic Economics and Conventional Economics (Comparative Study) with the following topics: (1) How is the theory of producer behaviour in Islamic and conventional economics? (2) What is the difference between the theory of producer behaviour in Islamic and conventional economics? The research that the author does is included in the research (Research library) in the form of library research that takes data from references, books, journals, and articles on the internet related to the problem. The results of the research conducted by the author can be conveyed as follows: (1) The theory of producer behaviour in Islamic economics that in creating a product or service, a producer does not only pay attention to what are human needs, but producers must also pay attention to the halal and haram of a product so as not to damage the morale of consumers. Furthermore, Islamic economics strongly encourages producers to improve the quality and welfare of the world and morals as business actors in creating happiness in the hereafter. Meanwhile, the theory of producer behaviour in the conventional economy does not pay attention to things like this. It only pays attention to how to generate maximum profits with small capital, which is very dominant. This is what causes a producer to ignore his social responsibilities. As the theory of theoretical rationality, where humans are called economically rational if they always maximize their interests, in conventional economics, the main motive of production is to maximize profits. (2) Comparison of the theories of producer behaviour in Islamic economics and conventional economics: The theories offered by Islamic economics are very different from the conventional concept of behaviour in terms of differences of opinion of scientists, their motivation, and goals in producing, and the concept. The theories observed by Islamic economic actors are monotheism, justice, freedom, belief, and halal. Penelitian ini membahas Teori Perilaku Produsen dalam Ekonomi Islam dan Ekonomi Konvensional (Studi Banding) dengan topik sebagai berikut: (1) Bagaimana teori perilaku produsen dalam ekonomi Islam dan konvensional? (2) Apa perbedaan antara teori perilaku produsen dalam ekonomi Islam dan konvensional? Penelitian yang penulis lakukan termasuk dalam penelitian (Research library) berupa penelitian kepustakaan yang mengambil data dari referensi, buku, jurnal, dan artikel di internet yang berhubungan dengan masalah. Hasil penelitian yang dilakukan penulis dapat disampaikan sebagai berikut: (1) Teori perilaku produsen dalam ekonomi Islam bahwa dalam menciptakan suatu produk atau jasa, seorang produsen tidak hanya memperhatikan apa yang menjadi kebutuhan manusia, tetapi produsen harus juga memperhatikan kehalalan dan keharaman suatu produk agar tidak merusak moral konsumen. Selanjutnya, ekonomi Islam sangat mendorong produsen untuk meningkatkan kualitas dan kesejahteraan dunia dan akhlak sebagai pelaku usaha dalam menciptakan kebahagiaan di akhirat. Sedangkan teori perilaku produsen dalam ekonomi konvensional tidak memperhatikan hal-hal seperti ini. Hanya memperhatikan bagaimana menghasilkan keuntungan yang maksimal dengan modal kecil yang sangat dominan. Hal inilah yang menyebabkan seorang produser mengabaikan tanggung jawab sosialnya. Sebagaimana teori rasionalitas teoritis, dimana manusia disebut rasional secara ekonomi jika selalu memaksimalkan kepentingannya, dalam ekonomi konvensional motif utama produksi adalah untuk memaksimalkan keuntungan. (2) Perbandingan teori perilaku produsen dalam ekonomi Islam dan ekonomi konvensional: Teori-teori yang ditawarkan oleh ekonomi Islam sangat berbeda dengan konsep perilaku konvensional dalam hal perbedaan pendapat para ilmuwan, motivasi dan tujuan mereka dalam berproduksi, dan konsep. Teori yang diamati oleh pelaku ekonomi Islam adalah tauhid, keadilan, kebebasan, keyakinan dan halal.